A Novel Handoff Necessity Estimation Approach Based on Travelling Distance - Jyoti Madaan; Indu Kashyap (Institute of Advanced Engineering and Science, 2018)
Mobility management is one of the most important challenges in Next Generation Wireless Networks (NGWNs) as it enables users to move across geographic boundaries of wireless networks. Nowadays, mobile communications have heterogeneous wireless networks offering variable coverage and Quality of Service (QoS). The availability of alternatives generates a problem of occurrence of unnecessary handoff that results in wastage of network resources. To avoid this, an efficient algorithm needs to be developed to minimize the unnecessary handoffs. Conventionally, whenever Wireless Local Area Network (WLAN) connectivity is available, the mobile node switch from cellular network to wireless local area network to gain maximum use of high bandwidth and low cost of wireless local area network as much as possible. But to maintain call quality and minimum number of call failure, a considerable proportion of these handovers should be determined. Our algorithm makes the handoff to wireless local area network only when the Predicted Received Signal Strength (PRSS) falls below a threshold value and travelling distance inside the wireless local area network is larger than a threshold distance.Through MATLAB simulation, we show that our algorithm is able to improve handover performance.